Pengaruh Sistem Informasi Akuntansi Penggajian Terhadap Pengendalian Internal Penggajian: Studi Pada Salah Satu Perusahaan Distributor Spare Part Sepeda Motor - Anisa Septiani; Maulana Yusup; Boy Suzanto; Anton Tirta Komara (Majalah Bisnis & IPTEK, 2021)
This study aims to determine the effect of payroll accounting information systems on payroll internal control. This study uses a quantitative approach with a survey approach to employees directly related to the accounting information system at a motorcycle spare part dealer in Badung City with 30 respondents. Using a simple linear regression analysis technique to determine the magnitude of the influence used the influence of the payroll accounting information system on payroll internal control. The calculation results show a positive influence of the payroll accounting information system on internal control of payroll with a total effect of 66.4%. The remaining 33.6% can influence by other factors not examined in the study.